2002
DOI: 10.1042/bj20011482
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the relevance of the glycan at Asn-52 of the α-subunit of human chorionic gonadotropin in the αβ dimer

Abstract: Glycosylation of Asn-52 of the alpha-subunit (alphaAsn-52) is required for bioactivity of the alphabeta-dimeric human chorionic gonadotropin (hCG), although at a molecular level the effect of the glycan at alphaAsn-52 is not yet understood. To study the role of this glycan for heterodimer stability, the beta-subunit was recombined in solution with either the alpha-subunit or the alpha-subunit enzymically deglycosylated at alphaAsn-52. Enzymic deglycosylation avoids modification of the glycans at alphaAsn-78 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…The present study on non-O-glycosylated phCG also shows that the O-glycosylation of β-hCG seems to have little influence on receptor binding and signal transduction, in accordance with earlier studies on urinary hCG [56]. In several studies, the importance of the N-glycosylation at Asn52 of urinary α-hCG for steroidogenic activity has been shown [56,57], and it has been postulated that the bulky and extended glycan at this site could have a function in inducing and stabilizing a conformational change in hCG upon binding to the receptor [58]. It is suggested that the high-mannose-type N-glycans on αAsn52 in phCG accomplish the same function.…”
Section: Discussionsupporting
confidence: 70%
“…The present study on non-O-glycosylated phCG also shows that the O-glycosylation of β-hCG seems to have little influence on receptor binding and signal transduction, in accordance with earlier studies on urinary hCG [56]. In several studies, the importance of the N-glycosylation at Asn52 of urinary α-hCG for steroidogenic activity has been shown [56,57], and it has been postulated that the bulky and extended glycan at this site could have a function in inducing and stabilizing a conformational change in hCG upon binding to the receptor [58]. It is suggested that the high-mannose-type N-glycans on αAsn52 in phCG accomplish the same function.…”
Section: Discussionsupporting
confidence: 70%
“…5), indicating differences in their solution conformations. Heterodimeric hCG exhibits two prominent (negative) CD bands at 207 nm and 196 nm, in agreement with published spectra (29,30). The CD spectra for YhCG1 and YhCG3 also exhibit a similar negative band at 207 nm, but there are significant differences between the two fusion proteins, and each differs from that of hCG.…”
Section: Resultssupporting
confidence: 85%
“…Hence, it appears that the carbohydrates are involved in subunit interaction and in maintaining a structure optimal for signal transduction. An alternate hypothesis suggested that the carbohydrates are required to stabilize a conformational change occurring as a consequence of receptor binding essential for signal transduction [30]. Our data indicate that the carbohydrates in the heterodimer may indeed be acting to stabilize the conformation of the heterodimer, be it a post-receptor binding acquired conformation or a conformation acquired due to subunit interaction.…”
Section: Discussionmentioning
confidence: 72%